KAJIAN MATEMATIS FITOREMEDIASI: PENENTUAN DISTRIBUSI KONSENTRASI MERKURI (Hg) PADA AKAR BAKAU (Rhizophora mucronata) MENGGUNAKAN METODE BEDA HINGGA - Nurhidayah, Nurhidayah; Jaya, A I; Ratianingsih, R (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2019)
The existence of mercury as a pollutant in the water environment caused by industrial activities and natural process can gives directly and indirectly impact to the marine life. As an example, it makes the reduction of water quality. Considering the mercury as the most dangerous pollutant, it would require a proper handling program to reduce the amount of mercury in the water environment. such as planting of hyperakumulator plant. Rhizophora mucronata is one of hyperakumulator plants that can absorb mercury effectively. This study discusses the distribution of mercury (Hg) concentrations in Rhizophora mucronata roots, that is investigated mathematically using diffusion model. The modification of the model is ð‘¢ð‘¡ = ð‘˜ð‘¢ð‘¥ð‘¥ + ð‘“(ð‘¥), where ð‘“(ð‘¥) states absorption roots function in absorbing mercury. A numerical scheme is derived by apply the finite difference method explicit scheme to get the numerical solutions. The simulation shows that the mercury concentrations is reduced from the root bark of the roots towards the central part. The difference of concentration distribution of mercury (Hg) in each layer, from the root bark of the roots towards the central part, will also decreases from the first week to the fifth week of time interval.Keywords : Diffusion Equations, Explicit Finite Difference Schemes, Mangrove, Mercury